Development of Teaching Materials for Single Move Arts Material for Pencak Silat Extracurricular Participants - Mega Purnawati mega; Herman Afrian; Zainul Arkanudin; Hariadi Hariadi; Rina Nopiana; Suryansah Suryansah (Musamus Journal of Physical Education and Sport (MJPES), 2024)
This research addresses the diminishing interest and enthusiasm of students in executing solo art movements, the insufficient facilities and infrastructure for teaching these movements effectively, the declining motivation among students to practice various forms of solo art, and the inadequate comprehension of developing solo movement techniques among students. Objective. Creation of instructional resources for individual art techniques for extracurricular participants of MA.Muallimat pencak silat, innovative methodologies for students, and the provision of contemporary approaches to ensure comprehension of the standard individual art techniques of pencak silat. Materials and Methods. The study employs the Research and Development (R&D) methodology. Data gathering methodologies and equipment employ product design, data validation, and product trials. Results. The guidebook is classified as "Good," based on an actual score of 0.04 derived from the examination of the value range 0.04 ˂ X 20.04. The trial outcomes were derived from observational data. The outcomes of the observations of learning activities utilising the handbook were conducted to enhance contemporary tactics for students, employing an observation instrument of 8 item statements. This field trial encompassed 25 students use the handbook. The analysis of conventional single art movements in pencak silat, conducted during a 7-day observation period utilising the handbook, yielded an average score of 06.2%, categorising it inside the BSH evaluation research (Developing according to expectations). Conclusion. The validation results from material experts indicate that the guidebook's quality, assessed by these experts, meets the "Good" criteria after conversion to a four-point scale, yielding a score of 3.3 and an average value of 3.18, which falls within the X range analysis greater than 1.8, thus confirming its suitability for data collection.